SERVICE LEVEL AGEREEMENTS A LEGAL AND PRACTICAL GUIDE - DESAI JIMMY (UNITED KINGDOM IT GOVERNANCE PUBLISHING, 2010)
Jimmy Desai$1 (Bs Service Level Agreements: A Legal and Practical Guide is a concise, practitioner-focused manual that helps organizations understand, design, and manage Service Level Agreements (SLAs) effectively. The book bridges both the legal and operational aspects of SLAs, making it useful for IT professionals, service managers, and corporate legal teams involved in outsourcing, vendor contracts, and service delivery management.s
SLA
INFORMATION TECHNOLOGY
ALL COMPUTER BRANCHES
Keywords: INFORMATION TECHNOLOGY; COMPUTER SCIENCE